2014
DOI: 10.1371/journal.pone.0086135
|View full text |Cite
|
Sign up to set email alerts
|

Arginase-1 Deficiency Regulates Arginine Concentrations and NOS2-Mediated NO Production during Endotoxemia

Abstract: Rationale and objectiveArginase-1 is an important component of the intricate mechanism regulating arginine availability during immune responses and nitric oxide synthase (NOS) activity. In this study Arg1fl/fl/Tie2-Cretg/− mice were developed to investigate the effect of arginase-1 related arginine depletion on NOS2- and NOS3-dependent NO production and jejunal microcirculation under resting and endotoxemic conditions, in mice lacking arginase-1 in endothelial and hematopoietic cells.Methods and ResultsArginas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 57 publications
3
50
0
1
Order By: Relevance
“…In fact, in a previous study with these mice, we observed effects of Arg1 ablation that could be attributed to either macrophages (cytokine production) or endothelium (NOS‐dependent effects on the mucosal perfusion of villi in the jejunum) (Wijnands et al. ). However, it is highly unlikely that substantial numbers of erythrocytes and macrophages were present in the walls of the vessels used in the wire‐myograph measurements.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In fact, in a previous study with these mice, we observed effects of Arg1 ablation that could be attributed to either macrophages (cytokine production) or endothelium (NOS‐dependent effects on the mucosal perfusion of villi in the jejunum) (Wijnands et al. ). However, it is highly unlikely that substantial numbers of erythrocytes and macrophages were present in the walls of the vessels used in the wire‐myograph measurements.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, we showed earlier that lipopolysaccharide‐treated Arg1‐KO Tie2 mice produced more NO in the endothelium of their carotid arteries and jejunum than control mice (Wijnands et al. ). In addition, Arg1‐KO Tie2 mice suffering from allergic asthma did not express ARG1 mRNA or protein in their lungs, even though this condition upregulates Arg1 expression >200‐fold in control mice (Cloots et al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ornithine is a precursor for polyamines and intermediates that give rise to collagen for wound healing and tissue repair (46). Moreover, BMDMs obtained from mice lacking arginase 1 are more susceptible to LPS-induced endotoxin as they show increased production of pro-inflammatory mediators as compared with BMDMs from wild-type mice (47). Various transcription factors have been shown to regulate arginase 1 expression in response to various stimuli.…”
Section: Nr4a2 Role In Inflammationmentioning
confidence: 99%
“…As arginine is a substrate for both endothelial and inducible nitric oxide synthase (eNOS, iNOS), nitric oxide (NO) synthesis rises with increasing arginine supply (Nagasaka et al 2009;Loscalzo 2003;Wijnands et al 2014). NO is a vasoprotective agent, regulating blood vessel diameter and compliance (Schulze et al 2004;Schulze et al 2006).…”
Section: Introductionmentioning
confidence: 99%